Analisis Spasial Berbasis Human Centered Design (HCD) dalam Optimalisasi Kepuasan Pengguna Mal Pelayanan Publik Siola - Marina, Nurul Fitria; Jiddan, Muhammad Jayyid (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
The Siola Public Service Mall (MPP) is a pioneering integrated service center in Surabaya that consolidates various bureaucratic functions into a single facility. However, transforming a historic building into a modern public space often encounters challenges in aligning user needs with existing spatial configurations. This study aims to analyze the spatial organization of MPP Siola through a Human-Centered Design (HCD) approach to optimize community satisfaction. The research employs a descriptive qualitative method, utilizing field observation (place-centered mapping) and questionnaires distributed to 100 service users. The analysis evaluates four key pillars of HCD: accessibility, thermal-visual comfort, wayfinding clarity, and spatial inclusivity. The findings indicate that while service integration operates effectively, there are critical issues regarding long linear circulation paths and a lack of intuitive signage, which contribute to reduced time efficiency for users. This study recommends a reconfiguration of waiting zones and the integration of biophilic elements as part of a humanistic design strategy to enhance psychological comfort. The results of this study are expected to serve as a reference for developing public service building designs that are more empathetic and responsive to contemporary community behavioral characteristics.